2014
DOI: 10.1038/onc.2014.107
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic models of pediatric brain tumors in zebrafish

Abstract: High-throughput screens (HTS) of compound toxicity against cancer cells can identify thousands of potential new drug-leads. But only limited numbers of these compounds can progress to expensive and labor intensive efficacy studies in mice, creating a ‘bottle-neck’ in the drug development pipeline. Approaches that triage drug-leads for further study are greatly needed. Here, we provide an intermediary platform between HTS and mice by adapting mouse models of pediatric brain tumors to grow as orthotopic xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…Gene expression patterns of cancer cells were shown to be highly similar in zebrafish and humans (Lam et al 2006;Zheng et al 2014). Similar molecular pathways may lead to tumor development in the two species (Jung et al 2013;Mione and Trede 2010) and tumors in zebrafish were found to be histologically similar to their mammalian counterparts (Armatruda et al 2002;Eden et al 2014;Stern and Zon 2003). Furthermore, zebrafish cells can respond to human signaling molecules (Drabsch et al 2013).…”
Section: Zebrafish In Cancer Research and The Tumor Xenotransplantatimentioning
confidence: 94%
See 4 more Smart Citations
“…Gene expression patterns of cancer cells were shown to be highly similar in zebrafish and humans (Lam et al 2006;Zheng et al 2014). Similar molecular pathways may lead to tumor development in the two species (Jung et al 2013;Mione and Trede 2010) and tumors in zebrafish were found to be histologically similar to their mammalian counterparts (Armatruda et al 2002;Eden et al 2014;Stern and Zon 2003). Furthermore, zebrafish cells can respond to human signaling molecules (Drabsch et al 2013).…”
Section: Zebrafish In Cancer Research and The Tumor Xenotransplantatimentioning
confidence: 94%
“…The absence of pigmentation aids microscopic observations because pigments in the embryo may conceal the fluorescence emitted by fluorescently labeled cells and only non-pigmented fish enable quantitative intravital fluorescence imaging of implanted cells. Despite its benefits, the Casper strain has rarely been used in xenotransplantation studies (Corkery et al 2011;Eden et al 2014). Instead, low concentrations of phenylthiourea (PTU) are often used to inhibit melanin synthesis (Lee et al 2009;Yang et al 2013aYang et al , 2013bYang et al , 2014.…”
Section: Growing Human Tumors Underwater: Approaches To Zebrafish Xenmentioning
confidence: 99%
See 3 more Smart Citations